Real-time imaging of Notch activation using a Luciferase Complementation-based Reporter - Ilagan, Ma. Xenia G. (2011)
Notch signaling regulates many cellular processes during development and adult tissue renewal. Upon ligand binding, Notch receptors undergo ectodomain shedding followed by γ-secretase-mediated release of the Notch intracellular domain (NICD), which translocates to the nucleus and associates with the DNA-binding protein CSL (CBF1/RBPjκ/Su(H)/Lag1) to activate gene expression. Mammalian cells contain four Notch receptors that can have both redundant and specific activities. To monitor activation of specific Notch paralogs in live cells and in real time, we developed luciferase complementation imaging (LCI) reporters for NICD/CSL association and validated them as a specific, robust and sensitive assay system that enables structure-function and pharmacodynamic analyses. Detailed kinetic analyses of various mechanistic aspects of Notch signaling, including nuclear translocation, γ-secretase and ADAM inhibition, as well as agonist- and ligand-dependent activation were conducted in live cells. Notch-LCI represents a powerful approach for characterizing modulators that target Notch signaling and for studying pathway dynamics in normal and disease contexts.